The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1152/ajpregu.00263.2001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of SGLT1 expression in response to Na+ intake

Abstract: In the chicken intestine, the reduction in Na+ intake led to a decrease in the transport of α-methyl-d-glucoside in the ileum (reduction of 42%) and in the rectum (51%). These reductions were reversed within 24 h after resalination and were inversely correlated to the changes in aldosterone plasma concentration. The reduction in intestinal hexose transport in the low Na+-fed animals was due to a decrease in the number of Na+-dependent d-glucose cotransporters (SGLT1) in the rectum (46%) and in the ileum (38%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
1
8
1
Order By: Relevance
“…(3) disappeared after either inhibition of ANG II synthesis or ANG II type 1 receptor (AT1) blockade. In addition, aldosterone regulates the expression of SGLT1 in the chicken intestine under low-sodium intake posttranscriptionally (2,22). In the present study, although we have not measured ANG levels, we have found an increase in the aldosterone levels in SHR when compared with WKY rats, which could be related with the observed changes in SGLT1 function and expression in the intestine of these rats.…”
Section: Discussioncontrasting
confidence: 56%
“…(3) disappeared after either inhibition of ANG II synthesis or ANG II type 1 receptor (AT1) blockade. In addition, aldosterone regulates the expression of SGLT1 in the chicken intestine under low-sodium intake posttranscriptionally (2,22). In the present study, although we have not measured ANG levels, we have found an increase in the aldosterone levels in SHR when compared with WKY rats, which could be related with the observed changes in SGLT1 function and expression in the intestine of these rats.…”
Section: Discussioncontrasting
confidence: 56%
“…Kojima et al (1999) also showed an increased expression of SGLT1 mRNA in the initial portion of jejunum in rats. However, Barfull et al (2002) did not find local differences in SGLT1 mRNA expression along the intestine of chickens. As the presence of SGLT1 mRNA alone did not establish the presence of the protein; western blotting and uptake studies were done to confirm that SGLT1 had a functional role along the small intestine.…”
Section: Discussionmentioning
confidence: 67%
“…For example, a high glucose diet and high sodium diet can increase the expression of intestinal SGLT1 on the transcriptional level [60, 61, 63]. The sweet taste receptor subunit T1R3 and the taste G protein gustducin, expressed in enteroendocrine L-cells, are involved in intestinal sensing of dietary sugar and artificial sweeteners which subsequently up-regulates intestinal SGLT1 mRNA and protein expression [64, 65].…”
Section: Luminal Nutrients Upregulate Intestinal Sglt1 Expressionmentioning
confidence: 99%